Immigration and the Expanding U.S. Southern Border: Casa en tierra ajena (2016) - Ewa Antoszek (European Journal of American Studies)
The question of the U.S.-Mexico border has been discussed extensively by various media in different contexts, particularly within the last few years and the focus of those publications has ranged from legislative issues, through militarization of the border and the resulting criminalization of migrants to the growing number of deportations and conditions in detention centers. Those exemplary cases of border stories related recently in the media signal the shift in immigration patterns from Central America and consequences of those changes for the whole region. They also demonstrate the trajectory of transformations at the U.S.-Mexico border, including the change of the concept of the border from la línea separating two nation-states into an ever-expanding zone that exceeds political lines and turns Mexico into the great south border. These issues are discussed in the documentary Casa en tierra ajena or Home in a Foreign Land (2016) directed by Ivannia Villalobos-Vindas and the purpose of the article is to examine how Villalobos-Vindas addresses the complexity of the process of forced migration from Central America and to analyze how the documentary illustrates the appearance of the expanding border or the transformation of the U.S.-Mexico political line into the great south border.